O Toque na Relação Terapêutica com a Pessoa Idosa - Carvalho, Sandra Alves (2007)
This qualitative and bibliographic study conducted in São Paulo has two objectives: understand the emotional and the sentimental aspects that the Touch has in the elderly treatment and support education policy makers in the use of this approach in the health treatment. For the study, it was chosen to use the participative observation in the treatment of five elderly persons, to who one open question was asked. This observation allowed the author to have a better perception about the importance of the Touch in the relation physiotherapy X elderly patience. The bibliographic part of this study, based on Montagu, Leakey, Mauss, Elias, Condillac, Guyton and Gardner theories, enables the understanding of the human being as a psychosocial being and the social and cultural experiences that build this human. It can be noticed, in this study, that the elderly loneness in our society is a recurring fact that leads to emotional problems, degenerating his/hers social relations. Because of that, the actuation model of the health professional should consider the Touch as a humanized tool in his/her work. And this tool should be used not only to improve the health condition, but also to help the psychosocial patience dimension